What Technology Can and Cannot Do to Support Assessment of Non-cognitive Skills - Simmering, Vanessa R.; Ou, Lu; Bolsinova, Maria (Frontiers in Psychology, 2019)
Advances in technology hold great promise for expanding what assessments may achieve across domains. We focus on non-cognitive skills as our domain, but lessons can be extended to other domains for both the advantages and drawbacks of new technological approaches for different types of assessments. We first briefly review the limitations of traditional assessments of non-cognitive skills. Next we discuss specific examples of technological advances, considering whether and how they can address such limitations, followed by remaining and new challenges introduced by incorporating technology into non-cognitive assessments. We conclude by noting that technology will not always improve assessments over traditional methods, and that careful consideration must be given to the advantages and limitations of each type of assessment relative to the goals and needs of the assessor. The domain of non-cognitive assessments in particular remains limited by lack of agreement and clarity on some constructs and their relations to observable behavior (e.g., self-control versus -regulation versus -discipline), and until these theoretical limitations must be overcome to realize the full benefit of incorporating technology into assessments.